Relevance of pineal gland: Science versus religion - Pratap Sanchetee; Suresh C Sanchetee (Wolters Kluwer Medknow Publications, 2018)
The pineal gland is a small but critical hormonal gland in our body. It is considered as a regulating or master gland that regulates the cycles within our bodies. Its purpose and function are still largely a mystery to science, and research on it is yielding very interesting discoveries, especially on its connection to spirituality and higher states of consciousness. Descriptions of the human anatomy derived from religious texts are often omitted from the medical literature. It may be that over time, science will validate many of these spiritual truths and statements as being based in scientific and medical fact.